2020
DOI: 10.3347/kjp.2020.58.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Chigger Mite Vectors for Tsutsugamushi Disease in the Hwaseong Area, Gyeonggi-do, Republic of Korea, 2015

Abstract: Owing to global climate change, the global resurgence of vector-borne infectious diseases and their potential to inflict widespread casualties among human populations has emerged as a pivotal burden on public health systems. Tsutsugamushi disease (scrub typhus) in the Republic of Korea is steadily increasing and was designated as a legal communicable disease in 1994. The disease is a mite-borne acute febrile disease most commonly contracted from October to December. In this study, we tried to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…These results indicated that A. agrarius was the dominant rodent host species for the surveyed chigger mites in the Hwaseong-si area. This dominancy of A. agrarius was consistent with the previously reported findings [ 18 , 19 ].…”
supporting
confidence: 93%
See 3 more Smart Citations
“…These results indicated that A. agrarius was the dominant rodent host species for the surveyed chigger mites in the Hwaseong-si area. This dominancy of A. agrarius was consistent with the previously reported findings [ 18 , 19 ].…”
supporting
confidence: 93%
“…agrarius was the dominant rodent host species for the surveyed chigger mites in the Hwaseong-si area. This dominancy of A. agrarius was consistent with the previously reported findings [18,19]. In this survey, a representative number of the chigger mites (n= 3,773, approximately 50% of the total collected chigger mites) were tested due to practical difficulties associated with examining all captured 7,531 chigger mites recovered from the captured field small mammals and the PCR experiments for the detection of for the 56-kDa type-specific antigen gene from O. tsutsugamushi (Supplementary Table S1).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Generally, tsutsugamushi disease is reported in late September and peaks in November in the Republic of Korea [ 3 ]. The essential feature of this disease is that it is arthropod-mediated, maintaining the infection in nature through the association among warm-blooded animals, such as humans and small wild mammals, such as mites, with the pathogen O. tsutsugamushi [ 4 ].…”
Section: Introductionmentioning
confidence: 99%